1998
DOI: 10.1038/sj.bjp.0702055
|View full text |Cite
|
Sign up to set email alerts
|

5‐Hydroxytryptamine receptors mediating vasoconstriction and vasodilation in perinatal and adult rabbit small pulmonary arteries

Abstract: 1 Vasoconstrictor responses to 5-HT, 5-carboxamidotryptamine (5-CT, 5-HT 1 receptor agonist), amethyl-5-HT (5-HT 2 receptor agonist) and sumatriptan (5-HT 1D/1B receptor agonist) were studied in fetal, 0 ± 24 h, 4 day, 7 day and adult rabbit pulmonary resistance arteries (PRAs), alone and in the presence of the NO synthase inhibitor N o -nitro-L-arginine methylester (L-NAME). The e ect of the selective 5-HT receptor antagonists ketanserin (5-HT 2A receptor) and GR55562 (5-HT 1B/1D receptor) on vasoconstrictor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…In contrast, inhibition of fetal 5-HT 1B receptors had no significant effect on fetal pulmonary blood flow, whereas 5-HT 2A receptor inhibition decreased PVR. Prior studies in isolated rabbit pulmonary arteries have shown that 5-HT-induced fetal pulmonary vasoconstriction is mediated through the 5-HT 2A receptor (40).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, inhibition of fetal 5-HT 1B receptors had no significant effect on fetal pulmonary blood flow, whereas 5-HT 2A receptor inhibition decreased PVR. Prior studies in isolated rabbit pulmonary arteries have shown that 5-HT-induced fetal pulmonary vasoconstriction is mediated through the 5-HT 2A receptor (40).…”
Section: Discussionmentioning
confidence: 99%
“…13,59,60 More precisely, related studies in rats report that hypoxia increased 5-HT 1B/D activity and promoted pharmacologic synergism with 5-HT 2A in PAs. 12,61 Related to this, the 5HT 1B/D receptor also is thought to be important to the development of pulmonary hypertension in rats and mice. 13,58 This leads to the possibility that the change in 5-HT potency and restriction of 5-HT 1B/Dmediated contraction observed in sheep may be beneficial adaptations to maternal LTH that restrain the development of pulmonary hypertension in the newborn.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Direct evidence of 5-HT as a causative agent for PPHN comes from recent studies demonstrating an increased risk of PPHN in infants born to mothers treated with selective serotonin reuptake inhibitors (SSRIs) during pregnancy. 10 Long-term hypoxia also enhances 5-HT-induced PA contraction in rats and mice [11][12][13] ; however, the mechanistic base of these changes is unclear. Nevertheless, 5-HT signaling is important for PA contraction and enhanced reactivity to this inflammatory substance is a feature of pulmonary hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…23) Histamine is also reported to exert pulmonary vasodilator actions preferentially during vasoconstriction and in other conditions of high PAP in animals [18][19][20] including rats. 20,24) However, our study showed no changes in PVR in response to histamine, indicating that histamine did not cause pulmonary vasoconstriction or vasodilatation in in vivo rat lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine causes pulmonary vasoconstriction in animals such as rabbits, 17,18) dogs, 19) cats, 20) guinea pigs, 21) pigs, 22) and horses. 23) Histamine is also reported to exert pulmonary vasodilator actions preferentially during vasoconstriction and in other conditions of high PAP in animals [18][19][20] including rats.…”
Section: Discussionmentioning
confidence: 99%